Partial tetrasomy 14 associated with multiple malformations. Issue 6 (23rd April 2013) - Winberg, Johanna; Lagerstedt Robinson, Kristina; Naess, Karin; Lesko, Nicole; Wibom, Rolf; Liedén, Agne; Anderlid, Britt‐Marie; Graff, Caroline; Nordenskjöld, Agneta; Nordgren, Ann; Gustavsson, Peter
Abstract We report on an 8‐year‐old female patient with multiple malformations including bilateral cleft lip and palate, coloboma, and craniosynostosis. She presented with severe intellectual disability, seizures, and gastrointestinal dysfunction. Mitochondrial investigations in a muscle biopsy revealed reduced activity in complex I of the mitochondrial respiratory chain. Chromosome analysis and fluorescent in situ hybridization (FISH) studies showed an isodicentric marker chromosome 14 that was identified in all cells analyzed in peripheral blood lymphocytes and cultured fibroblasts. Parental chromosome studies were normal. To further characterize the marker chromosome and determine its origin, we performed array‐based comparative genomic hybridization (CGH) and polymorphic marker analysis with quantitative fluorescent PCR (QF‐PCR). The combined results from cytogenetic and array‐CGH analyses showed tetrasomy 14p13q13.1 and results from the QF‐PCR point to formation of the marker chromosome in the maternal meiosis. Isodicentric chromosomes involving partial 14q have previously been reported in four cases; however, this is the first patient with tetrasomy 14p13q13.1 in non‐mosaic form surviving beyond infancy. © 2013 Wiley Periodicals, Inc.